Learning Effects of Problem-Identification and Problem-Solving Internships - Kunieda, Yoshiaki; Nunome, Akihiro; Chotechaung, Naruphun; Fujii, Tsumugi (Advances in Social Sciences Research Journal, 2025)
We aim to understand the features and educational impacts of problem-identification and problem-solving internships (hereinafter called ‘problem-solving internships’) at the National Institute of Technology, Toyama College. Problem-solving internship is a practical internship style that emphasizes experience in which intern students examine and propose solutions to actual business problems faced by a company. Thus, we qualitatively analysed the reports submitted by participating students using the steps for coding and theorisation (SCAT) method. The results of the qualitative analysis by SCAT indicate that problem-solving internships provide a variety of learning and growth opportunities for students. The analysis showed that students can acquire different perspectives by reaffirming their social roles and abilities and by collaborating with individuals who have different values. It was also found that overcoming anxiety and participating in a problem-solving internship provides a chance to reflect on one’s own potential and future challenges. These findings highlight the significant influence of the internship’s pre-design and implementation on student learning, suggesting possibilities for further improvement and application of the educational program.